Effects of Resistance Training on Matrix Metalloproteinase Activity in Skeletal Muscles and Blood Circulation During Aging - de Sousa Neto, Ivo V.; Durigan, João L. Q.; Guzzoni, Vinicius; Tibana, Ramires A.; Prestes, Jonato; de Araujo, Heloisa S. Selistre; Marqueti, Rita de Cássia (Frontiers in Physiology, 2018)
Aging is a complex, multifactorial process characterized by the accumulation of deleterious effects, including biochemical adaptations of the extracellular matrix (ECM). The purpose of this study was to investigate the effects of 12 weeks of resistance training (RT) on metalloproteinase 2 (MMP-2) activity in skeletal muscles and, MMP-2 and MMP-9 activity in the blood circulation of young and old rats. Twenty-eight Wistar rats were randomly divided into four groups (n=7 per group): young sedentary (YS); young trained (YT), old sedentary (OS) and old trained (OT). The stair climbing RT consisted of one training session every 2 other day, with 8–12 dynamic movements per climb. The animals were euthanized 48h after the end of the experimental period. MMP-2 and MMP-9 activity was measured by zymography. There was higher active MMP-2 activity in the lateral gastrocnemius and flexor digitorum profundus muscles in the OT group when compared to the OS, YS and YT groups (p ≤ 0.001). Moreover, there was higher active MMP-2 activity in the medial gastrocnemius muscle in the OT group when compared to the YS and YT groups (p ≤ 0.001). The YS group presented lower active MMP-2 activity in the soleus muscle than the YT, OS, OT groups (p ≤ 0.001). With respect to active MMP-2/9 activity in the bloodstream, the OT group displayed significantly reduced activity (p ≤ 0.001) when compared to YS and YT groups. In conclusion, RT up-regulates MMP-2 activity in aging muscles, while down-regulating MMP-2 and MMP-9 in the blood circulation, suggesting that it may be a useful tool for the maintenance of ECM remodeling.